Sirolimus in renal transplant recipients with malignancies in Germany - Naik, Marcel G.; Arns, Wolfgang; Budde, Klemens; Diekmann, Fritz; Eitner, Frank; Gwinner, Wilfried; Heyne, Nils; Jurgensen, Jan Steffen; Morath, Christian; Riester, Udo; Heller, Katharina M.; Fischereder, Michael (Clinical Kidney Journal, 2021)
Background. Renal transplant recipients have an increased cancer risk. The mammalian target of rapamycin inhibitor sirolimus (SRL) has immunosuppressive and antitumour activities but knowledge about its use in recipients with cancer is limited.
CRIS-Team WoS Importer:2021-10-01